Preparation, characterization, and lead removal appraisal of zinc aluminate prepared at different calcination temperatures . - Latiff, M I A; Nuruzzaman, D M; Basri, S; Ismail, N M; Jamaludin, S N S; Kamaruzaman, F F
The present research study deals with the preparation of 6-layered functionally graded (FG) metal-ceramic composite materials through powder metallurgy technique. Using a cylindrical die-punch set made of steel, the nickel-alumina (Ni-Al2O3) graded composite structure was fabricated. The samples consist of four gradual inter layers of varied nickel composition (80wt.%, 60wt.%, 40wt.%, 20wt.%) sandwiched with pure Ni and Al2O3 powders at the ends (100wt.% and 0wt.% nickel) were fabricated under 30 ton compaction load using a hydraulic press. After that, two-step sintering was carried out at sintering temperature 1200ºC and soaking time 3 hours was maintained in a tube furnace. The properties of the prepared samples were characterized by radial shrinkage, optical microscopy and hardness testing. Results showed that larger shrinkage occurred within the ceramic phase which proves that more porosities were eliminated in the ceramic rich layers. From the microstructural analysis, it was observed that alumina particles are almost uniformly distributed in nickel matrix, so as nickel particles in the ceramic matrix of alumina-dominant layers. From interfacial analyses, it was observed that a smooth transition in microstructure from one layer to the next confirms a good interfacial solid state bonding between metal-ceramic constituents and good compaction process. On the other hand, microhardness test results suggest that there might be increasing percentage of porosities in the graded structure as the ceramic content rises .